IBADAH DAN PRAKTIKNYA DALAM MASYARAKAT - Husna, Khotimatul; Arif, Mahmud (TA’LIM : Jurnal Studi Pendidikan Islam, 2021)
Worship gives peace of mind to its adherents, worship also makes the distance between God and humans close. Indonesian people in performing religious rituals or what is commonly referred to as worship have their own way, usually, there is a sector sect in Islam that makes Muslims worship different ways according to the guidelines held, although they have differences in practising worship, Muslims still within the established scope of the law. This study aims to find out how Muslims pray and the differences. This research uses the literature review method. The results in this study, praying in a way that is believed by each individual according to the guidelines they hold respectively. The differences in performing these worship procedures exist and do not make Muslims divided because both have a foundation in doing so.